Kontribusi Sertifikasi Guru, Motivasi Kerja, dan Supervisi Akademik Terhadap Kinerja Guru Sekolah Dasar di Gugus III Kecamatan Penebel Kabupaten Tabanan - Ni Wayan Yulastiningtiyas; Ni Luh Gede Erni Sulindawati; Basilius Redan Werang (LP. Ma'arif Janggan Magetan, 2024)
This study aims to (1) describe the contribution of teacher certification to the performance of elementary school teachers in Cluster III, Penebel District, Tabanan Regency, (2) describe the contribution of work motivation to the performance of elementary school teachers in Cluster III, Penebel District, Tabanan Regency, (3) describe the contribution of academic supervision to the performance of elementary school teachers in Cluster III, Penebel District, Tabanan Regency, (4) describe the contribution of teacher certification, work motivation, and academic supervision together to the performance of elementary school teachers in Cluster III, Penebel District, Tabanan Regency. This study is an